The Persistent South: Southern Distinctiveness, Cultural Identity, and Change - Frederick, Jeff (European Scientific Journal, ESJ, 2017)
In recent years, contemporary observers and scholars have argued that the distinctiveness of the American South has vanished. Historians sympathetic to this view have cited various causal factors including political shifts, economic changes, migration and demographic data, the rise of a suburban South, racial reconciliation, or a general sentiment that the North and South were always more alike than different. Southern exceptionalism, it is argued, is either gone or never was as significant as previously indicated. In fact, the operative and most persistent characteristics of the South have been cultural, not political or economic. As a result, reports of the distinctive South’s demise have been premature. An examination of archetypal southern cultural characteristics such sport, food, gender, and presuppositions about family and faith indicate that the South in fact remains very much different from the rest of the country. Even elements of southern political culture remain relatively steadfast, most notably a predilection toward the politics of victimization. Despite the fall of the Confederacy, the end of slavery, the decline of the Solid Democratic South, and the comparative diminution of overt racial politics, northerners and southerners continue to manifest cultural differences and recognize these in each other. Southern culture persists.